T14. HYPOTHALAMIC-PITUITARY-GONADAL AXIS HORMONES IN ANTIPSYCHOTIC NAïVE FIRST-EPISODE OF PSYCHOSIS AND HEALTHY CONTROLS. (18th May 2020) - Teresa Pons-Cabrera, Maria; Sagué-Vilavella, Maria; González-Rodríguez, Alexandre; Madero, Santiago; Vázquez, Mireia; Soler-Catà, Victòria; Fernández-Egea, Emilio; Kirkpatrick, Brian; Labad, Javier; Bernardo, Miquel; García-Rizo, Clemente
Abstract: Background: Kraepelin (1909) wrote about the association between female sex hormones and psychotic symptoms. He observed that women diagnosed with schizophrenia showed signs of gonadal dysfunction and hypoestrogenism. Antipsychotic drugs had not yet been introduced, so it cannot be interpreted as side effects. At the beginning of the 20th-century rhythmicity of psychotic symptoms through menstrual cycle was observed. The symptoms ameliorated when higher levels of estrogens were found. It was also noted during pregnancy. Reported cases and some studies confirmed these observations. Epidemiology shows a later peak of onset of psychosis in women. This protective role, also observed in clinical and animal studies, remains for the reproductive years and decreases by the time of menopause, when there's a second important peak of onset in women. In spite of all these observations, few systematic investigations have been published about the effects of estrogens in women with schizophrenia. This study aims to investigate differences in the levels of sexual hormones between antipsychotic-naïve women with and without psychosis. Methods: We performed a retrospective case-control study to compare the levels of sex hormones in blood of first-episode psychosis (FEP) and healthy control women (HC) of reproductive age, as a part of a NIH-NIDDK project on the study of hormonal factors and metabolism in psychosis. All participants were antipsychotic-naïve, in order to avoid bias from antipsychotic medication use. Four cases and four controls were recruited: cases were women newly diagnosed with primary non-affective psychosis at the emergency department of our hospital, and controls were mental health workers of similar age with no history of psychosis. Blood samples were obtained at the luteal phase of the menstrual cycle. We registered the following variables: age, psychosis status, last menstrual day and hormone blood levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol and progesterone. We used descriptive statistics for age and hormone blood levels (mean and standard deviation -SD-) and we performed the Kruskal-Wallis test to determine any statistical differences of these variables regarding psychosis status. All participants provided informed consent. Ethical approval was obtained from the institutional ethics review board. Results: The mean age of FEP was 31.4 years (SD 1.9) and 26.1 years (SD 3.5) for HC, with no statistically significant differences. Both FSH and LH were higher in FEP (FSH: mean 7 U/L, SD 1.7; LH: mean 8.4 U/L, SD 2.6) compared to HC (FSH: mean 3.5 U/L, SD 1.2; LH: mean 5.7 U/L, SD 3.3), reaching statistical significance in the case of FSH (p=0.015). 17-b-estradiol was lower in FEP (mean 75.3 pg/mL, SD 54.6) than in HC (mean 151 ng/mL, SD 102.1), although differences were not statistically significant Discussion: We observed higher levels of FSH in women with psychosis compared to controls in the luteal phase. These women were antipsychotic-naïve; thus, these results are not a consequence of medication use. Our observations add evidence to the known relationship between altered hormonal levels and schizophrenia in women. The increase in FSH stimulates the production of estrogens, which are known to be low in psychosis compared to healthy controls. This finding supports the hypoestrogenism hypothesis of schizophrenia. Future studies with larger samples evaluating hormonal levels, psychotic symptoms and differences with hormonal treatments could lead to research of new adjunctive therapies or approaches.